2017
DOI: 10.1002/kin.21104
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Uncatalyzed Reactions of 2,4′- and 4,4′-Diphenylmethane-Diisocyanate with Primary and Secondary Alcohols

Abstract: The kinetics of the uncatalyzed reaction of an industrially important 50/50 blend of isomers of 4,4′‐diphenylmethane‐diisocyanate (4,4‐MDI) and 2,4′‐diphenylmethane‐diisocyanate (2,4′‐MDI) with primary and secondary alcohols was studied using high‐performance liquid chromatography coupled with photodiode array detector. The alcohols such as 1‐propanol, 2‐propanol, 1‐hexanol, 2‐hexanol, 3‐hexanol, 1‐methoxy‐2‐propanol, and 3‐methoxy‐1‐propanol were used in high molar excess to diisocyanate in toluene at 80°C, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
(38 reference statements)
4
15
0
Order By: Relevance
“…Alcohols containing ether groups such as DEGME and 3‐MeO show decreased reactivity towards 2,6‐TDI. Similar observations were found for the reaction of 4,4‘‐ diphenylmethane‐diisocyanate (4,4‘‐MDI) and 2,4‐TDI with DEGME and 3‐MeO. Furthermore, secondary alcohols, most likely due to a steric effect, were observed to react ca.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Alcohols containing ether groups such as DEGME and 3‐MeO show decreased reactivity towards 2,6‐TDI. Similar observations were found for the reaction of 4,4‘‐ diphenylmethane‐diisocyanate (4,4‘‐MDI) and 2,4‐TDI with DEGME and 3‐MeO. Furthermore, secondary alcohols, most likely due to a steric effect, were observed to react ca.…”
Section: Resultssupporting
confidence: 80%
“…As seen in Figure , under the applied chromatographic conditions, all of the products formed in the reaction are well separated, thus making quantification of these compounds possible. Furthermore, both in this study and in our previous reports,, the UV‐Vis properties of aromatic carbamates are found to be strongly independent of the reacting alcohols; that is, the molar absorption coefficient is the same for each product formed by methanol quenching. Hence, the corresponding molar fraction for the products can easily be calculated as shown in the Experimental section.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The products of the methanol-quenched reactions are denoted as XDI_1,3, XDI_1,3R, and XDI_1R,3R. In order to calculate the relative concentrations of the products, i.e., the corresponding molar fractions (X i ), the peak areas obtained from HPLC-PDA measurements at λ = 210 nm were used similarly to those reported in our previous works [17,18]. The molar fractions of the unreacted (X XDI_1,3 ), the one-substituted (X XDI_1,3R , one of two isocyanate groups has reacted) and the two-substituted (X XDI_1R,3R , both isocyanate groups has reacted) 1,3-XDI come as given by Equations (1)- 3:…”
Section: Assessment Of the Kinetic Datamentioning
confidence: 99%
“…In this work, the following tasks were performed: (i) The effect of the length of the alkyl chain of primary alcohols on the reaction rate coefficient. (ii) The reactivity of 1,3-XDI towards alcohols and polyols, especially concerning those of MDI and TDI (To obtain comparable kinetic data, the same reaction conditions were used in this study as those applied for other diisocyanate-alcohol reactions [17,18]). (iii) Prediction of the product distribution in the 1,3-XDI-polyol reactions using the kinetic data obtained in the reaction of 1,3-XDI with alcohol mimicking the chain-end of the given polyol.…”
Section: Introductionmentioning
confidence: 99%